Evaluation of cloves (Syzygium aromaticum) against antibiotics resistant Vibrio parahaemolyticus on seafood - Nillian, Elexson; Rukayadi, Yaya; Nakaguchi, Yoshitsugu; Nishibuchi, Mitsuaki; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
Vibrio parahaemolyticus is a main foodborne disease in seafood and generally seafood is easily deteriorates in quality of color and flavor. In this study, clove (Syzygium aromaticum) extract shows potent antibacterial activity against growth of antibiotics resistant Vibrio parahaemolyticus on seafood samples (cockles and shrimps). Vibrio parahaemolyticus was artificial contaminates on the samples with 106 CFU/ml. The samples were treated with different concentration of cloves extract with 10 mg/ml which are 0.5%, 5% and 10% concentration from methanol food grade extraction in 0 hr, 5 min, 10 min, 15 min, 30 min, 60 min and 120 min. Tab water and deionized water were selected as a negative control. As a result, the amount of 10 % cloves managed to mitigates the number of V. parahaemolyticus on seafood samples in 5 minutes and 15 min on both samples. Therefore, our results signify the fact that cloves can be apply as natural sanitizer which could meet consumer demands for safe and traditionally consumed either raw without any undesirable effect when applied in the seafood system industries.